Factors associated with speeding behavior of Moroccan drivers: Study guided by the theory of planned behavior - Abderrahim El Hafidy; Taoufik Rachad; Ali Idri (IATSS Research)
This study investigates the determinants that influence drivers to exceed speed limits by using an extended version of the Theory of Planned Behavior (TPB). Therefore, data about 254 drivers representing various cities in Morocco were collected via a web-based questionnaire. Then, confirmatory factor analysis (CFA) was used to validate the proposed questionnaire, while structural equation modeling (SEM) was conducted to analyze and validate the hypothesized model. The results suggest that the extended TPB, incorporating additional factors of habit, moral norms and descriptive norms, outperforms the original TPB. Moreover, the findings underscore that speeding behavior is directly influenced by both speeding intention and habit, and indirectly influenced by moral norms and habit through the mediation of intention. The result of this study will contribute to developing new behavior change interventions aiming at combating speeding behavior and also contributing to ongoing efforts aiming at promoting road safety.